Pengaruh Lingkungan Kerja, Beban Kerja Dan Human Relations Terhadap Kinerja Pegawai Pada Dinas Pemberdayaan Perempuan, Perlindungan Anak, Pengendalian Penduduk Dan Keluarga Berencana (DP3AP2KB) Kabupaten Probolinggo - Khotimah, Nur; Widayanto, Mutinda Teguh; Haidaputri, Trivosa Aprilia Novadiana (Universitas Panca Marga, 2024)
Employee performance is very important because it is a reflection of the agency's ability to achieve predetermined goals. One of the factors that influence employee performance is the work environment, workload and human relations. This research aims to determine the influence of the work environment, workload and human relations on employee performance simultaneously, partially and determine the dominant variables on employee performance. This research method is quantitative with an associative approach. The population of this research is all employees, totaling 41 employees. The data collection technique uses saturated sampling. The sample was 41 respondents. Data was collected through questionnaires. Data analysis techniques include validity testing, reliability testing, classical assumption testing, multiple regression analysis, coefficient of determination (R2) and hypothesis testing. The research results show that the work environment, workload and human relations simultaneously and partially have a significant and significant effect on employee performance. The dominant variable in this research is the work environment.